2015
DOI: 10.4103/0366-6999.151663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Desmopressin on Platelet Aggregation and Blood Loss in Patients Undergoing Valvular Heart Surgery

Abstract: Background:Blood loss after cardiac surgery can be caused by impaired platelet (PLT) function after cardiopulmonary bypass. Desmopressin or 1-deamino-8-D-arginine vasopressin (DDAVP) is a synthetic analog of vasopressin. DDAVP can increase the level of von Willebrand factor and coagulation factor VIII, thus it may enhance PLT function and improve coagulation. In this study, we assessed the effects of DDAVP on PLT aggregation and blood loss in patients undergoing cardiac surgery.Methods:A total of 102 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 11 publications
2
23
0
2
Order By: Relevance
“…A recent double-blind RCT (n ¼ 102) tested the effects of DDAVP on postoperative blood loss and platelet aggregation. 221 The intervention group was treated with 0.3 mg kg À1 during surgery and a control group received saline. The results showed a significant decrease in postoperative blood loss and FFP transfusions in the DDAVP group during the first 6 h post-surgery (the duration of drug activity).…”
Section: Desmopressinmentioning
confidence: 99%
“…A recent double-blind RCT (n ¼ 102) tested the effects of DDAVP on postoperative blood loss and platelet aggregation. 221 The intervention group was treated with 0.3 mg kg À1 during surgery and a control group received saline. The results showed a significant decrease in postoperative blood loss and FFP transfusions in the DDAVP group during the first 6 h post-surgery (the duration of drug activity).…”
Section: Desmopressinmentioning
confidence: 99%
“…It is the preferred treatment for VWD-related bleeding [125][126][127]. Clinical studies have shown that DDAVP improves postoperative platelet function and bleeding time in uremic patients [128], improves platelet aggregation in patients taking aspirin and/orclopidogrel [129][130][131], and reduces postoperative bleeding in cardiac patients taking aspirin [132,133], with very low incidences of cardiovascular and cerebral vascular thrombosis complications [134]. DDAVP (0.4 μ/kg iv over 30 min) may be given in cases of cerebral hemorrhage in patients receiving antiplatelet drugs or in cases of injury in VWD patients [135,136].…”
Section: Recommendation 18: Desmopressin Improves Platelet Function Imentioning
confidence: 99%
“…Results showed no significant difference between the two groups desmopressin and control. In addition, no significant difference was found between the two groups in terms of mechanical ventilation duration, cardiovascular side effects and ICU hospitalization .…”
Section: Discussionmentioning
confidence: 82%
“…Desmopressin shortens PTT and bleeding time (BT) although increased amounts of factor VIII and von Willebrand factor (vWF) are involved in the intrinsic pathway of coagulation and haemostasis . Desmopressin has no effect on the platelet number or aggregation; however, it strengthens the platelet adhesion to the vessel wall . Complications reported for desmopressin include mild facial flushing, headache, palpitations and hypotension .…”
mentioning
confidence: 99%